Knocking out central metabolism genes to identify new targets and alternating substrates to improve lipid synthesis in Y. lipolytica - Zhu, Jiang; Gu, Yang; Yan, Yijing; Ma, Jingbo; Sun, Xiaoman; Xu, Peng (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Systematic gene knockout studies may offer us novel insights on cell metabolism and physiology. Specifically, the lipid accumulation mechanism at the molecular or cellular level is yet to be determined in the oleaginous yeast Y. lipolytica. Methods: Herein, we established ten engineered strains with the knockout of important genes involving in central carbon metabolism, NADPH generation, and fatty acid biosynthetic pathways. Results: Our result showed that NADPH sources for lipogenesis include the OxPP pathway, POM cycle, and a trans-mitochondrial isocitrate-α-oxoglutarate NADPH shuttle in Y. lipolytica. Moreover, we found that knockout of mitochondrial NAD+ isocitrate dehydrogenase IDH2 and overexpression of cytosolic NADP+ isocitrate dehydrogenase IDP2 could facilitate lipid synthesis. Besides, we also demonstrated that acetate is a more favorable carbon source for lipid synthesis when glycolysis step is impaired, indicating the evolutionary robustness of Y. lipolytica. Discussion: This systematic investigation of gene deletions and overexpression across various lipogenic pathways would help us better understand lipogenesis and engineer yeast factories to upgrade the lipid biomanufacturing platform.